Impact of Game Crops Intensification and Hunting Management on Red-Legged Partridge - Fancoise Ponce-Boutin; Jean-Francois Mathon; Tanguy Le Brun (National Quail Symposium Proceedings, 2017)
In the French Mediterranean region, large cultivated areas have been abandoned. Matorrals (shrublands) then woodland successional stages replace the mosaic of habitats, favourable to the red-legged Partridge Alectoris rufa. An agro-environmental operation, consisting of development of areas devoted to game crops, allowed the reopening of these landscapes on the studied site. This we followed by the development of a hunting plan and operation. We tested the impact of these managements on the dynamics of the red-legged partridge abundance. Our research showed that the limitation of hunting bag has a strong impact on the densities of partridge in spring, whereas habitat managements act favourably on the success of the reproduction and recruitment.
Keywords: Alectoris rufa; breeding success; brood size; game crop; habitat management; hunting management; French Mediterranean region; red-legged partridge; population dynamics; rural abandonment